Composite powder with carbon nanotubes adsorbed on surface of silicon dioxide, preparation method of composite powder and silicon dioxide reinforced copper-based composite material
By connecting the amino group on the silicon surface and binding to the carbon nanotubes, the mesh structure is formed, and the problem of insufficient binding of silicon dioxide and copper -based interface interface has significantly improved the mechanics and friction performance of composite materials.
Patent Information
- Application Number
- CN202411488684.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
The interface bonding force between silica and copper matrix is insufficient, resulting in low mechanical and frictional properties of the composite material.
The branch of the silica surface is divided with a carboxyl group on the carbon nanotuba to form a mesh carbon nanotuba structure, improves the moisture between the silicon and the copper -based body, thereby improving its binding force.
By improving the combination of interface, the mechanical performance and friction performance of silicon -based composite composite materials is significantly improved, including improvement of hardness, density, and tensile strength.
Smart Images

Figure CN119370852A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-based composite materials, and in particular to a composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide and a preparation method thereof, and a silicon dioxide-reinforced copper-based composite material. Background Art
[0002] Silica-copper composite materials have the excellent properties of copper and silica, such as good thermal conductivity, electrical conductivity, excellent ductility and other mechanical properties of copper, and high hardness and high wear resistance of silica. They are widely used in the fields of automobile manufacturing, rail transportation, electronics and electrical engineering, and other electrical contact materials. However, due to the poor mutual wettability between the surfaces of silica and copper and the large difference in thermal expansion coefficients, the strength of the two when combined is low. When under load, due to poor interface bonding, silica exists in the form of impurities, which greatly reduces the mechanical properties of the composite material.
[0003] In order to improve the bonding between the silica and copper interface, the main method currently used is to alloy the silica surface, such as copper plating on the silica surface, but simple surface alloying has limited effect on the performance improvement of the composite material. The method of multi-component reinforced phase hybrid reinforced composite material provides another way to solve the interface problem. The newly introduced components improve the performance of the composite material while changing the interface problem between the silica and the copper matrix, which requires that the newly introduced components can exist between the silica and the copper matrix. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a composite powder of carbon nanotubes adsorbed on the surface of silica and a preparation method thereof, and a silica-reinforced copper-based composite material. First, amino groups are grafted on the surface of silica and combined with carboxyl groups on carbon nanotubes to form a layer of mesh carbon nanotube structure on the surface of silica. When the mesh carbon nanotubes are combined with a copper matrix, the wettability between silica and the copper matrix is improved, so that the obtained silica-carbon nanotube-copper composite material has a higher density and hardness, while improving the bonding force between the copper matrix and silica, thereby greatly improving the mechanical properties and friction properties of the silica-reinforced copper-based composite material.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a composite powder of carbon nanotubes adsorbed on a silicon dioxide surface, the method comprising the following steps:
[0007] (1) calcining the clean silica powder raw material;
[0008] (2) modifying the surface of the silicon dioxide calcined in step (1) with amino groups to functionalize it, thereby obtaining functionalized silicon dioxide;
[0009] (3) immersing the carbon nanotubes in an etching acid solution for etching, so that carboxyl groups are grafted onto the surface of the carbon nanotubes to obtain carbon nanotubes with surface modified carboxyl groups; dispersing the etched carbon nanotubes in anhydrous ethanol to obtain a carbon nanotube dispersion;
[0010] (4) mixing the carbon nanotubes in the carbon nanotube dispersion obtained in step (3), the functionalized silica obtained in step (2), a dehydrating agent, and a stabilizer, and allowing the amino groups on the silica and the carboxyl groups on the carbon nanotubes to dehydrate and combine under stirring conditions to form amide bonds, so that the carbon nanotubes are adsorbed on the surface of the silica, thereby obtaining the composite powder of carbon nanotubes adsorbed on the surface of the silica.
[0011] Furthermore, in step (1), the particle size of the silica powder raw material is controlled at 5-15 μm; the silica powder raw material is washed with deionized water before calcination, and the raw material is allowed to settle for 2-3 minutes after each washing, and the number of washing times is 5-10 times.
[0012] Furthermore, in step (1), the calcination temperature is 100-200° C., the calcination time is 1-3 hours, and after calcination, the product is stored in a constant temperature drying oven.
[0013] Furthermore, in step (2), a silane coupling agent is used to modify silica so that amino groups are grafted on its surface; the silane coupling agent is 3-aminopropyltriethoxysilane (APTES); the modification process is: preparing an alcohol solution of a silane coupling agent with a concentration of 5-15 ml / L (prepared by dissolving the silane coupling agent in anhydrous ethanol), placing the calcined silica in a condensation reflux device, and adding the prepared alcohol solution of the silane coupling agent, reacting under stirring at 65-70° C. for 5-30 hours; after the reaction, washing with anhydrous ethanol and storing in a constant temperature drying oven to obtain silica with amino groups grafted on its surface, thereby realizing the functionalization of silica.
[0014] Furthermore, in step (3), the etching acid solution is a solution obtained by mixing sulfuric acid and nitric acid in a volume ratio of 4:1, the etching time is 8-12 hours, and the etching temperature is 45-50°C; the concentrations of the sulfuric acid and nitric acid used are both 95-98wt.%.
[0015] Furthermore, in step (3), the ratio of the carbon nanotubes to the etching acid solution is (1-3) g:50 mL.
[0016] Furthermore, the specific process of step (4) is as follows: weigh a certain amount of the carbon nanotube dispersion prepared in step (3), add it to a certain amount of deionized water, then add a dehydrating agent and a stabilizer, and stir the resulting mixture for 1-3 hours (carbon nanotube activation time) to activate the carbon nanotubes; then add the functionalized silica obtained in step (2), stir at 20-30° C. for 15-60 minutes (dehydration time), and after stirring the product obtained after the reaction, wash it with anhydrous ethanol and dry it to obtain the composite powder of carbon nanotubes adsorbed on the surface of the silica; wherein: the dehydrating agent and the stabilizer are added to the mixture, and the mixture is stirred for 1-3 hours (carbon nanotube activation time) to activate the carbon nanotubes; then add the functionalized silica obtained in step (2), stir at 20-30° C. for 15-60 minutes (dehydration time), and after stirring the product obtained after the reaction, wash it with anhydrous ethanol and dry it to obtain the composite powder of carbon nanotubes adsorbed on the surface of the silica; wherein: The aqueous solution is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS), and the stabilizer is morpholineethanesulfonic acid (MES); the EDC concentration in the mixed material is 2-8 g / L, the NHS concentration is 0.5-2 g / L, and the MES concentration is 0.5-2 g / L (the concentration ratio of EDC, NHS and MES in the mixed material is preferably 4:1:1); the weight ratio of the carbon nanotubes to the functionalized silicon dioxide in the carbon nanotube dispersion is (0.01-0.10):1.
[0017] In the silicon oxide surface adsorbed carbon nanotube composite powder prepared by the above method, the carbon nanotubes are interwoven into a network and uniformly attached to the surface of silicon dioxide, and agglomeration occurs less frequently; the weight ratio of carbon nanotubes to silicon dioxide is (0.01-0.10):1.
[0018] The prepared composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide is used to further prepare a silicon dioxide reinforced copper-based composite material. The preparation process is as follows: the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide is mixed evenly with copper powder, cold-pressed in a mold and then sintered to obtain the silicon dioxide reinforced copper-based composite material in which silicon dioxide is evenly distributed in a copper matrix; in the composite material, carbon nanotubes serve as bridges to connect silicon dioxide and the copper matrix.
[0019] Furthermore, the weight ratio of the carbon nanotube composite powder adsorbed on the surface of silicon dioxide to the copper powder is (0.5-1.0): (29.0-29.5); the pressure applied during the cold pressing is 35-50 MPa, and the pressing time is 5-20 min; the sintering process is spark plasma sintering, and the vacuum degree during the plasma sintering is 13 -2 -10 -2 Pa, sintering pressure 35-50MPa, sintering temperature 600-800℃, sintering time 5-15min.
[0020] The design mechanism and beneficial effects of the present invention are as follows:
[0021] 1. The present invention fully mixes silicon dioxide with an appropriate amount of carbon nanotubes adsorbed on the surface with copper powder, and obtains a copper-based composite material of silicon dioxide-carbon nanotube hybrid reinforcement through cold pressing and sintering. The composite material has high hardness and high density. At the same time, due to the network structure formed by the carbon nanotubes on the surface of silicon dioxide, the interface bonding between silicon dioxide and the copper matrix is improved, so that when the composite material is stretched, the influence of silicon dioxide as a crack extension source on the reduction of tensile strength is reduced, and the influence of silicon dioxide as a defect is also reduced, which can effectively improve the tensile strength of the composite material.
[0022] 2. In the silicon dioxide-reinforced copper-based composite material prepared by the present invention, the presence of silicon dioxide greatly improves the hardness of the composite material, and the network structure of carbon nanotubes ensures that the elongation of the composite material will not be greatly reduced.
[0023] 3. In the silica-reinforced copper-based composite material prepared by the present invention, since carbon nanotubes are anti-friction materials, they are easy to produce a self-lubricating film during the friction process to reduce wear, thereby effectively improving the mechanical properties and anti-friction and wear resistance of the silica-carbon nanotube-reinforced copper-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are SEM images of the silicon dioxide surface after carbon nanotubes are adsorbed on the surface of the present invention; wherein: (a) Example 1; (b) Example 3.
[0025] Figure 2 This is a metallographic image of the silicon dioxide reinforced copper-based composite material prepared in Example 1;
[0026] Figure 3 This is a diagram of the interface bonding between the silicon dioxide-carbon nanotube composite powder particles and the copper matrix in the copper-based composite material prepared in Example 1.
[0027] Figure 4 for Figure 3 EDS spectra of various points in the image.
[0028] Figure 5 The tensile fracture SEM images of the copper-based composite materials prepared in Example 1 and Comparative Example 1; wherein: (a) Example 1; (b) Comparative Example 1. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0031] Example 1
[0032] This embodiment provides a silicon dioxide-carbon nanotube hybrid reinforced copper-based composite material, and the preparation process thereof is as follows:
[0033] 1. Preparation of functionalized silica:
[0034] Prepare a silica powder raw material with a particle size of about 10 μm, and wash it first. The process is: mix the silica with deionized water and stir, then let it stand for 3 minutes, take the precipitated silica, and repeat the washing step 7 times.
[0035] The cleaned silica was calcined in a muffle furnace for 120 min at a temperature of 120°C.
[0036] Prepare an APTES alcohol solution with a concentration of 10 ml / l: dissolve 4 ml of 3-aminopropyltriethoxysilane (APTES) in a certain amount of anhydrous ethanol to prepare a total of 400 ml of an APTES alcohol solution with a concentration of 10 ml / l.
[0037] Place 4 g of calcined silica into a condensation reflux device, add 400 ml of the prepared APTES alcohol solution and stir continuously while maintaining 70°C. After stirring for 15 hours, wash twice with anhydrous ethanol and store in a drying oven overnight to obtain silica with surface grafted amino groups.
[0038] 2. Preparation of functionalized carbon nanotubes:
[0039] Take 1g of carbon nanotubes and put them into a beaker. Take 40ml of concentrated sulfuric acid (purity 98%) and 10ml of concentrated nitric acid (purity 98%) and mix them and pour them into the beaker. Use a constant temperature magnetic stirrer to stir and keep the temperature at 50°C. After 10 hours, dilute the etched product with deionized water, and then use a centrifuge to centrifuge and stratify the diluted material. Then dilute and centrifuge it multiple times until the mixed solution is neutral. Then take out the stratified carbon nanotubes (grafted with carboxyl groups) and disperse them in a certain amount of anhydrous ethanol to obtain a carbon nanotube dispersion with surface grafted carboxyl groups.
[0040] 3. Preparation of silicon dioxide-carbon nanotube composite powder:
[0041] Weigh a certain amount of the carbon nanotube dispersion with surface grafted carboxyl groups prepared in step 2 (containing 0.027 g of carbon nanotubes with surface grafted carboxyl groups), put it into 100 ml of deionized water, add 0.4 g of EDC, 0.1 g of NHS, and 0.1 g of MES into the water and stir for 2 hours, then take 0.9 g of the functionalized silica prepared in step 1, add it thereto, and stir for 30 minutes. During this period, due to the action of the dehydrating agent, the amino groups on the silica and the carboxyl groups on the carbon nanotubes will be dehydrated and combined to form amide bonds. After the stirring is completed, the reaction product is washed twice with anhydrous ethanol and placed in a vacuum drying oven overnight to obtain a composite powder of carbon nanotubes adsorbed on the surface of silica (silicon dioxide-carbon nanotube composite powder).
[0042] 4. Preparation of silica-carbon nanotube-copper composite material: 0.9 g silica-carbon nanotube composite powder was mixed with 29.1 g copper powder, and the mixed powder was fully mixed and then cold pressed using a cold press machine for 10 min at a pressure of 5 MPa.
[0043] The green body obtained after cold pressing is subjected to spark plasma sintering. The sintering process parameters are: vacuum degree is 13 -2 -10 -2 Pa, increase the pressure to 50 MPa at a pressure increase rate of 10 MPa / min, and maintain the pressure at this pressure for 5 minutes; then increase the temperature to 600°C, a sintering temperature, at a heating rate of 100°C / min, and maintain at 50 MPa and 600°C for 10 minutes; when the temperature in the furnace cools to below 250°C, release the hydraulic pressure, and then cool to room temperature to obtain a silica-carbon nanotube-copper composite material, that is, a silica-reinforced copper-based composite material.
[0044] Figure 1 (a) is a scanning electron microscope image of the silicon dioxide-carbon nanotube composite powder prepared in this example. It can be seen that after sufficient adsorption, the carbon nanotubes are uniformly attached to the surface of the silicon dioxide without a large amount of agglomeration. Figure 2 This is a metallographic image of the silicon dioxide reinforced copper-based composite material prepared in this example. It can be seen that silicon dioxide is evenly distributed in the copper matrix. Figure 3 This is an enlarged view of the interface between the silicon dioxide-carbon nanotube composite powder particles and the copper matrix in the metallographic phase diagram of the copper-based composite material prepared in this embodiment. Figure 4 for Figure 3The EDS energy spectra of each point in the graph are respectively in the copper matrix near the silicon dioxide, at the interface between the silicon dioxide and the copper matrix, and on the silicon dioxide surface. In the energy spectrum, only copper and carbon elements can be observed at point 1, indicating that part of the carbon nanotubes are embedded in or distributed in the copper matrix, while carbon, silicon and oxygen can be observed at point 4, indicating that the carbon nanotubes are also adsorbed on the silicon dioxide surface, and copper, silicon, oxygen, carbon and other elements can be observed at points 2 and 3, indicating that the carbon nanotubes exist between the silicon dioxide and the copper matrix as a bridge connecting the silicon dioxide and the copper matrix. Figure 5 (a) is a scanning image of the fracture surface of the copper-based composite material in this example. Carbon nanotubes were observed between the silicon dioxide and the copper matrix, proving that Figure 4 The presence of carbon.
[0045] Example 2
[0046] This embodiment is a copper-based composite material with added silicon dioxide composite powder with carbon nanotubes adsorbed on the surface. Compared with Example 1, the carbon nanotubes adsorbed on the surface of silicon dioxide in this embodiment are one third of that in Example 1. The specific preparation process is as follows:
[0047] 1. Preparation of functionalized silica:
[0048] Prepare a silica powder raw material with a particle size of about 10 μm, and wash it first. The process is: mix the silica with deionized water and stir, then let it stand for 3 minutes, take the precipitated silica, and repeat this washing step 7 times.
[0049] The cleaned silica was calcined in a muffle furnace for 120 min at a temperature of 120°C.
[0050] Prepare an APTES alcohol solution with a concentration of 10 ml / l: Dissolve 4 ml of 3-aminopropyltriethoxysilane (APTES) in a certain amount of anhydrous ethanol to prepare a total of 400 ml of an APTES alcohol solution with a concentration of 10 ml / l.
[0051] 4 g of calcined silica was placed in a condensation reflux device, and 400 ml of the prepared APTES alcohol solution was added and stirred continuously, and the temperature was kept at 70°C. After stirring for 15 hours, the solution was washed twice with anhydrous ethanol and stored in a drying oven overnight to obtain silica with surface grafted amino groups.
[0052] 2. Preparation of functionalized carbon nanotubes:
[0053] 1 g of carbon nanotubes was placed in a beaker, 40 ml of concentrated sulfuric acid (purity 98%) and 10 ml of concentrated nitric acid (purity 98%) were mixed and poured into the beaker, and stirred with a constant temperature magnetic stirrer, and the temperature was maintained at 50° C. After 10 hours, the etched product was diluted with deionized water, and the diluted material was centrifuged and layered using a centrifuge, followed by multiple dilutions and multiple centrifugations until the mixed solution was neutral, and then the layered carbon nanotubes (grafted with carboxyl groups) were taken out and dispersed in a certain amount of anhydrous ethanol to obtain a dispersion of carbon nanotubes with surface grafted carboxyl groups;
[0054] 3. Preparation of silicon dioxide-carbon nanotube composite powder:
[0055] Take 0.009 g of the functionalized carbon nanotubes in step 2, put them into 100 ml of deionized water, add 0.4 g of EDC, 0.1 g of NHS, and 0.1 g of MES into the water and stir for 2 h, then take 0.9 g of the functionalized silica prepared in step 1, add it thereto, and stir for 30 min. During this period, due to the action of the dehydrating agent, the amino groups on the silica and the carboxyl groups on the carbon nanotubes will be dehydrated and combined to form amide bonds. After the stirring is completed, the reaction product is washed twice with anhydrous ethanol and placed in a vacuum drying oven overnight to obtain a composite powder with carbon nanotubes adsorbed on the silica surface (silicon dioxide-carbon nanotube composite powder).
[0056] 4. Preparation of silica-carbon nanotube-copper composite material: 0.9 g silica-carbon nanotube composite powder was mixed with 29.1 g copper powder. After sufficient mixing, the mixed powder was cold pressed using a cold press for 10 min at a pressure of 5 MPa.
[0057] The green body obtained after cold pressing is subjected to spark plasma sintering. The sintering process parameters are: vacuum degree is 13 -2 -10 -2 Pa, increase the pressure to 50 MPa at a pressure increase rate of 10 MPa / min, and maintain the pressure at this pressure for 5 minutes; then increase the temperature to 600°C, a sintering temperature, at a heating rate of 100°C / min, and maintain at 50 MPa and 600°C for 10 minutes; when the temperature in the furnace cools to below 250°C, release the hydraulic pressure, and then cool to room temperature to obtain a silica-carbon nanotube-copper composite material, that is, a silica-reinforced copper-based composite material.
[0058] Example 3
[0059] This example is a copper-based composite material reinforced by hybrid silicon dioxide and carbon nanotubes. Compared with Example 1, the carbon nanotubes adsorbed in this example are twice that of Example 1. The specific preparation process is as follows:
[0060] 1. Preparation of functionalized silica:
[0061] Prepare a silica powder raw material with a particle size of about 10 μm, and wash it first. The process is: mix the silica with deionized water and stir, then let it stand for 3 minutes to remove the precipitated silica, and repeat this step 7 times.
[0062] The cleaned silica was calcined in a muffle furnace for 120 min at 120 °C.
[0063] Prepare an APTES alcohol solution with a concentration of 10 ml / l: Dissolve 4 ml of 3-aminopropyltriethoxysilane (APTES) in a certain amount of anhydrous ethanol to prepare a total of 400 ml of an APTES alcohol solution with a concentration of 10 ml / l.
[0064] Place 4 g of calcined silica into a condensation reflux device, add 400 ml of the prepared APTES alcohol solution and stir continuously while maintaining 70°C. After stirring for 15 hours, wash twice with anhydrous ethanol and store in a drying oven overnight to obtain silica with surface grafted amino groups.
[0065] 2. Preparation of functionalized carbon nanotubes:
[0066] 1 g of carbon nanotubes was placed in a beaker, 40 ml of concentrated sulfuric acid (purity 98%) and 10 ml of concentrated nitric acid (purity 98%) were mixed and poured into the beaker, and stirred with a constant temperature magnetic stirrer, and the temperature was maintained at 50° C. After 10 hours, the etched product was diluted with deionized water, and the diluted material was centrifuged and layered using a centrifuge, followed by multiple dilutions and multiple centrifugations until the mixed solution was neutral, and then the layered carbon nanotubes (grafted with carboxyl groups) were taken out and dispersed in a certain amount of anhydrous ethanol to obtain a dispersion of carbon nanotubes with surface grafted carboxyl groups;
[0067] 3. Preparation of silicon dioxide-carbon nanotube composite powder:
[0068] Take the carbon nanotube dispersion with surface grafted carboxyl groups prepared in step 2 (containing 0.054 g of carbon nanotubes with surface grafted carboxyl groups), put it into 100 ml of deionized water, add 0.4 g of EDC, 0.1 g of NHS, and 0.1 g of MES into the water and stir for 2 hours, then take 0.9 g of functionalized silica prepared in step 1, add it to the water, and stir for 30 minutes. During this period, due to the action of the dehydrating agent, the amino groups on the silica and the carboxyl groups on the carbon nanotubes will be dehydrated and combined to form amide bonds. After the stirring is completed, the reaction product is washed twice with anhydrous ethanol and placed in a vacuum drying oven overnight to obtain a silica composite powder with carbon nanotubes adsorbed on the silica surface (silicon dioxide-carbon nanotube composite powder).
[0069] 4. Preparation of silica-carbon nanotube-copper composite material: 0.9 g silica-carbon nanotube composite powder was mixed with 29.1 g copper powder. After being fully mixed, the mixed powder was cold pressed by a cold press machine for 10 min at a pressure of 5 MPa.
[0070] The green body obtained by cold pressing is sintered by spark plasma with a vacuum degree of 13 -2 -10 -2 Pa, increase the pressure to 50 MPa at a pressure increase rate of 10 MPa / min, and maintain the pressure at this pressure for 5 minutes; then increase the temperature to 600°C, a sintering temperature, at a heating rate of 100°C / min, and maintain at 50 MPa and 600°C for 10 minutes; when the temperature in the furnace cools to below 250°C, release the hydraulic pressure, and then cool to room temperature to obtain a silica-carbon nanotube-copper composite material, that is, a silica-reinforced copper-based composite material. Figure 1 (b) is a scanning electron microscope image of the silicon dioxide-carbon nanotube composite powder prepared in this example. It can be seen that after sufficient adsorption, the carbon nanotubes are uniformly attached to the surface of the silicon dioxide.
[0071] Example 4
[0072] This embodiment provides a silicon dioxide-carbon nanotube hybrid reinforced copper-based composite material. Compared with Example 1, the carbon nanotubes adsorbed in this embodiment are three times that of Example 1. The specific preparation process is as follows:
[0073] 1. Preparation of functionalized silica:
[0074] Prepare a silica powder raw material with a particle size of about 10 μm, and wash it first. The process is: mix the silica with deionized water and stir, then let it stand for 3 minutes to remove the precipitated silica, and repeat this step 7 times.
[0075] The cleaned silica was calcined in a muffle furnace for 120 min at 120 °C.
[0076] Prepare an APTES alcohol solution with a concentration of 10 ml / l: dissolve 4 ml of 3-aminopropyltriethoxysilane (APTES) in a certain amount of anhydrous ethanol to prepare a total of 400 ml of an APTES alcohol solution with a concentration of 10 ml / l.
[0077] Place 4 g of calcined silica into a condensation reflux device, add 400 ml of the prepared APTES alcohol solution and stir continuously while maintaining 70°C. After stirring for 15 hours, wash twice with anhydrous ethanol and store in a drying oven overnight to obtain silica with surface grafted amino groups.
[0078] 2. Preparation of functionalized carbon nanotubes:
[0079] Take 1g of carbon nanotubes and put them into a beaker. Take 40ml of concentrated sulfuric acid (purity 98%) and 10ml of concentrated nitric acid (purity 98%) and mix them and pour them into the beaker. Use a constant temperature magnetic stirrer to stir and keep the temperature at 50°C. After 10 hours, dilute the etched product with deionized water and use a centrifuge to centrifuge and stratify the diluted material. Then dilute and centrifuge it multiple times until the mixed solution is neutral. Then take out the stratified carbon nanotubes (grafted with carboxyl groups) and disperse them in a certain amount of anhydrous ethanol to obtain a dispersion of carbon nanotubes with surface grafted carboxyl groups.
[0080] 3. Preparation of silicon dioxide-carbon nanotube composite powder:
[0081] Take the carbon nanotube dispersion with surface grafted carboxyl groups prepared in step 2 (containing 0.081 g of carbon nanotubes with surface grafted carboxyl groups), put it into 100 ml of deionized water, add 0.4 g of EDC, 0.1 g of NHS, and 0.1 g of MES into the water and stir for 2 h, then take 0.9 g of the functionalized silica prepared in step 1, add it into the water, and stir for 30 min, during which the amino groups on the silica and the carboxyl groups on the carbon nanotubes will dehydrate and combine to form amide bonds due to the effect of the dehydrating agent, after the stirring is completed, wash the reaction product twice with anhydrous ethanol and store it in a vacuum drying oven overnight to obtain a composite powder with carbon nanotubes adsorbed on the silica surface (silicon dioxide-carbon nanotube composite powder);
[0082] 4. Preparation of silica-carbon nanotube-copper composite material: 0.9 g silica-carbon nanotube composite powder was mixed with 29.1 g copper powder. After being fully mixed, the mixed powder was cold pressed by a cold press machine for 10 min at a pressure of 5 MPa.
[0083] The green body obtained after cold pressing was sintered by spark plasma sintering at a vacuum degree of 13 -2 -10 -2 Pa, increase the pressure to 50 MPa at a pressure increase rate of 10 MPa / min, and maintain the pressure at this pressure for 5 minutes; then increase the temperature to 600°C, a sintering temperature, at a heating rate of 100°C / min, and maintain at 50 MPa and 600°C for 10 minutes; when the temperature in the furnace cools to below 250°C, release the hydraulic pressure, and then cool to room temperature to obtain a silica-carbon nanotube-copper composite material, that is, a silica-reinforced copper-based composite material.
[0084] Comparative Example 1
[0085] This comparative example provides a silicon dioxide reinforced copper-based composite material whose surface is not adsorbed with carbon nanotubes. Compared with Example 1, steps (2) and (3) are not performed. In order to compare with the above example, the silicon dioxide used in this comparative example is still functionalized, and only the carbon nanotubes are not adsorbed on the surface. The specific preparation process is as follows:
[0086] 1. Preparation of functionalized silica:
[0087] Prepare a silica powder raw material with a particle size of about 10 μm, and wash it first. The process is: mix the silica with deionized water and stir, then let it stand for 3 minutes to remove the precipitated silica, and repeat this step 7 times.
[0088] The cleaned silica was calcined in a muffle furnace for 120 min at 120 °C.
[0089] Prepare an APTES alcohol solution with a concentration of 10 ml / l: dissolve 4 ml of 3-aminopropyltriethoxysilane (APTES) in a certain amount of anhydrous ethanol to prepare a total of 400 ml of an APTES alcohol solution with a concentration of 10 ml / l.
[0090] Place 4 g of calcined silica into a condensation reflux device, add 400 ml of the prepared APTES alcohol solution and stir continuously while maintaining 70°C. After stirring for 15 hours, wash twice with anhydrous ethanol and store in a drying oven overnight to obtain silica with surface grafted amino groups.
[0091] 2. Preparation of silica-reinforced copper-based composite materials: 0.9 g of the functionalized silica powder prepared in step 1 was mixed with 29.1 g of copper powder. After being fully mixed, the mixed powder was cold-pressed using a cold press for 10 min at a pressure of 5 MPa.
[0092] The cold pressed green body was sintered by spark plasma sintering. The sintering process parameters were: vacuum degree 13 -2 -10 -2 Pa, increase the pressure to 50 MPa at a pressure increase rate of 10 MPa / min, and maintain the pressure at this pressure for 5 minutes; then increase the temperature to sintering temperature of 600°C at a heating rate of 100°C / min, and maintain at 50 MPa and 600°C for 10 minutes; when the temperature in the furnace cools to below 250°C, release the hydraulic pressure, and then cool to room temperature to obtain a silica-reinforced copper-based composite material.
[0093] The fracture of the copper-based composite material prepared in this comparative example is as follows Figure 5 As shown in (b), it can be seen that there are no carbon nanotubes connected at the joints between the copper substrate and the silicon dioxide.
[0094] Comparative Example 2
[0095] This comparative example provides a copper-based composite material reinforced with silicon dioxide having no carbon nanotubes adsorbed on the surface. Compared with Example 1, steps (2) and (3) are not performed, and the silicon dioxide used in the comparative example is not functionalized. The specific preparation process is as follows:
[0096] 1. Calcination of silicon dioxide:
[0097] Prepare silica powder raw material with a particle size of about 10 μm, and wash it first. The process is: mix silica with deionized water and stir, then let it stand for 3 minutes, take the precipitated silica, and repeat this step 7 times. Use a muffle furnace to calcine the washed silica for 120 minutes at a temperature of 120°C.
[0098] 2. Preparation of silica-reinforced copper-based composite material: 0.9 g silica powder was mixed with 29.1 g copper powder. After being fully mixed, the mixed powder was cold pressed by a cold press machine for 10 min at a pressure of 5 MPa.
[0099] The cold pressed green body was sintered by spark plasma sintering. The sintering process parameters were: vacuum degree 13 -2 -10 -2 Pa, increase the pressure to 50 MPa at a pressure increase rate of 10 MPa / min, and maintain the pressure at this pressure for 5 minutes; then increase the temperature to sintering temperature of 600°C at a heating rate of 100°C / min, and maintain at 50 MPa and 600°C for 10 minutes; when the temperature in the furnace cools to below 250°C, release the hydraulic pressure, and then cool to room temperature to obtain a silica-reinforced copper-based composite material.
[0100] Performance Testing:
[0101] The composite materials prepared in the above examples and comparative examples were tested for relative density, Brinell hardness, tensile strength and average friction coefficient, wherein:
[0102] Relative density: that is, density, which is the ratio of actual density to theoretical density;
[0103] Brinell hardness test: using HB-3000B Brinell hardness tester, the loading force is 125N, the holding time is 15s, and the indenter diameter is 10mm;
[0104] Tensile strength test: using Instron 5982 electronic universal material testing machine, the tensile speed is 0.1mm / min;
[0105] Average friction coefficient test: measured using Rtec-MFT-5000-H multifunctional friction and wear testing machine;
[0106] The test results are summarized in Table 1.
[0107] Table 1 Performance characterization results of silica reinforced copper matrix composites
[0108]
[0109] The relative density, Brinell hardness, friction coefficient and tensile strength of the copper-based composite materials prepared in the above-mentioned embodiments and comparative examples were tested, and the results are shown in the following table. It can be seen from the table that compared with the copper-based composite materials prepared in the comparative examples, the copper-based composite materials reinforced with silica-carbon nanotube particles prepared in each embodiment have higher Brinell hardness and lower friction coefficient. At the same time, it can be seen from the table that the copper-based composite materials reinforced with silica-carbon nanotube particles prepared in each embodiment can significantly enhance the tensile strength, especially the tensile strength of Example 1 is 297.20MPa, compared with the copper-based composite materials in the comparative examples, the tensile strength of the composite material is increased by 15.06%.
[0110] By comparing the performance of Example 1 with that of Comparative Example 1, it is found that the adsorption of carbon nanotube composite powder on the surface of silicon dioxide can effectively improve the comprehensive performance of the material. This is because the adsorption of carbon nanotubes on the surface can improve the interface bonding between silicon dioxide and the copper matrix ( Figure 3 and Figure 4 ). Comparing the performance of Example 1 with Example 2 and Comparative Example 1, it is found that the copper-based composite material enhanced by silicon dioxide adsorbing carbon nanotubes has better comprehensive performance. Comparing the performance of Example 1 with Example 2, Example 3 and Example 4, it is found that the adsorption amount of carbon nanotubes should be 2-4%, and the copper-based composite material has better comprehensive performance.
[0111] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide, characterized in that: The preparation method comprises the following steps: (1) calcining the clean silica powder raw material; (2) modifying the surface of the silicon dioxide calcined in step (1) with amino groups to functionalize it, thereby obtaining functionalized silicon dioxide; (3) immersing the carbon nanotubes in an etching acid solution for etching to graft carboxyl groups onto the surface of the carbon nanotubes, and dispersing the etched carbon nanotubes in anhydrous ethanol to obtain a carbon nanotube dispersion; (4) mixing the carbon nanotubes in the carbon nanotube dispersion obtained in step (3), the functionalized silica obtained in step (2), a dehydrating agent, and a stabilizer, and allowing the amino groups on the silica and the carboxyl groups on the carbon nanotubes to dehydrate and combine under stirring to form amide bonds, thereby obtaining the composite powder of carbon nanotubes adsorbed on the surface of silica.
2. The method for preparing the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide according to claim 1, characterized in that: In step (1), the particle size of the silica powder raw material is controlled at 5-15 μm; the silica powder raw material is washed with deionized water before calcination, and the raw material is allowed to settle for 2-3 minutes after each washing, and the washing frequency is 5-10 times.
3. The method for preparing the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide according to claim 1, characterized in that: In step (1), the calcination temperature is 100-200° C. and the calcination time is 1-3 h.
4. The method for preparing the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide according to claim 1, characterized in that: In step (2), a silane coupling agent is used to modify silica so that amino groups are grafted on its surface; the silane coupling agent is 3-aminopropyltriethoxysilane (APTES); the modification process is: preparing an alcohol solution of the silane coupling agent with a concentration of 5-15 ml / l, placing the calcined silica in a condensation reflux device, and adding the prepared alcohol solution of the silane coupling agent, reacting under stirring at 65-70° C. for 5-30 hours; after the reaction, washing with ethanol and drying, obtaining silica with amino groups grafted on its surface, thereby realizing the functionalization of silica.
5. The method for preparing the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide according to claim 1, characterized in that: In step (3), the etching acid solution is a solution obtained by mixing sulfuric acid and nitric acid in a volume ratio of 4:1, the etching time is 8-12 hours, and the etching temperature is 45-50°C; the concentrations of the sulfuric acid and nitric acid used are both 95-98wt.%.
6. The method for preparing the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide according to claim 5, characterized in that: In step (3), the ratio of the carbon nanotubes to the etching acid solution is (1-3) g:50 mL.
7. The method for preparing the composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide according to claim 1, characterized in that: The specific process of step (4) is as follows: weigh a certain amount of the carbon nanotube dispersion prepared in step (3), add it to a certain amount of deionized water, then add a dehydrating agent and a stabilizer, and stir the resulting mixture for 1-3 hours (carbon nanotube activation time) to activate the carbon nanotubes; then add the functionalized silica obtained in step (2), stir for 15-60 minutes (dehydration time), and after stirring the reaction, wash the resulting product with anhydrous ethanol and dry it to obtain the carbon nanotube composite adsorbed on the surface of the silica. Powder; wherein: the dehydrating agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS), and the stabilizer is morpholineethanesulfonic acid (MES); the EDC concentration in the mixed material is 2-8 g / L, the NHS concentration is 0.5-2 g / L, and the MES concentration is 0.5-2 g / L; the weight ratio of the carbon nanotubes to the functionalized silica in the carbon nanotube dispersion is (0.01-0.10):
1.
8. A composite powder of carbon nanotubes adsorbed on the surface of silicon dioxide prepared by the method according to any one of claims 1 to 7, characterized in that: In the composite powder, carbon nanotubes are interwoven into a network and uniformly attached to the surface of silicon dioxide; the weight ratio of carbon nanotubes to silicon dioxide is (0.01-0.10):
1.
9. A silica-reinforced copper-based composite material prepared by using the silica surface adsorbed carbon nanotube composite powder as claimed in claim 8, characterized in that: The preparation process of the copper-based composite material is as follows: the carbon nanotube composite powder adsorbed on the surface of silicon dioxide is mixed evenly with copper powder, cold-pressed in a mold and then sintered to obtain the silicon dioxide-reinforced copper-based composite material in which silicon dioxide is evenly distributed in a copper matrix.
10. The silicon dioxide reinforced copper-based composite material according to claim 9, characterized in that: The weight ratio of the carbon nanotube composite powder adsorbed on the surface of silicon dioxide and the copper powder is (0.5-1.0): (29.0-29.5); the pressure applied in the cold pressing is 35-50MPa, and the pressing time is 5-20min; the sintering treatment is spark plasma sintering, and the vacuum degree is 13 -2 -10 -2 Pa, sintering pressure 35-50MPa, sintering temperature 600-800℃, sintering time 5-15min.
Citation Information
Cited By
Production process of high-purity nano silicon dioxide
CN122102145A